Development of synthetic-oil palm hybrid fiber reinforced mortar - Dellrianna Durai (2022)
This research use oil palm fibre (OPF) as a natural fiber, crumb rubber aggregate, superplasticizer, and synthetic fiber to study the physical and mechanical strength reinforced mortar. The mechanical properties of mortar were identified with addition 0.6% cement by weight for oil palm fiber and synthetic fiber, 5%, 10% and 15% fine aggregate partial replacement by weight for rubber crumb, and 0.4%, 0.6% and 0.8% of superplasticizer. The composite mixtures were subjected to the compression strength test, split tensile strength test and flexural strength tests. A total of 13 mix proposition has been done for this research. There were 117 sample for compression strength, 117 sample for split tensile test and 117 sample for flexural strength has been done in this research with the total of 351 sample. The result was then analysed to identify the effect of crumb rubber, oil-palm fiber and synthetic fiber to the mortar matrix. Addition of fiber and crumb rubber in the mortar matrix significantly decrease the workability of the mix. The strength of the mortar also shown to be directly proportional to the crumb rubber and fiber content. The addition of 0.6% synthetic fiber to the composite was found to improve the split tensile strength of the mortar composites.